2021
DOI: 10.37506/ijfmt.v16i1.17644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Motivational Interviewing on the Self-Efficacy of Type 2 Diabetes Mellitus Patients

Siska Puji Lestari,
Titin Andri Wihastuti,
Dina Dewi Sartika Lestari Ismail

Abstract: Diabetes mellitus is a metabolic disease that cannot be fully cured, thereby needing continuous treatment. As poor lifestyles increase in number and variation, the prevalence of diabetes mellitus is increasing every year. The purpose of this study is to determine the effects of motivational interviewing on the self-efficacy of type 2 diabetes mellitus patients. This study is an experimental study using Non-Randomized Control Group Pretest Posttest Design. The population was type 2 diabetes mellitus patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The fact that this score was much lower, especially among the control group, suggests that as physical exercise requires time and requires behavioral changes, the participants did not have enough motivation to instigate this behavior change. Similar studies to the present research have also demonstrated an increase in the scores of the Self-Efficacy Scale and its subdimensions (Lestari et al, 2022). Regarding the initiation and maintenance of self-efficacy in diabetes management, associated cognitive processes and their effects via the employment of Pender-based motivational interviewing, it is suggested that perceived self-management regarding diabetes management, the effects of important activity, and increased self-efficacy perceptions have been facilitated by inventions designed to invoke healthy lifestyle behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that this score was much lower, especially among the control group, suggests that as physical exercise requires time and requires behavioral changes, the participants did not have enough motivation to instigate this behavior change. Similar studies to the present research have also demonstrated an increase in the scores of the Self-Efficacy Scale and its subdimensions (Lestari et al, 2022). Regarding the initiation and maintenance of self-efficacy in diabetes management, associated cognitive processes and their effects via the employment of Pender-based motivational interviewing, it is suggested that perceived self-management regarding diabetes management, the effects of important activity, and increased self-efficacy perceptions have been facilitated by inventions designed to invoke healthy lifestyle behaviors.…”
Section: Discussionsupporting
confidence: 92%